2019
DOI: 10.1002/jso.25494
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy for management of the N0 neck in oral cavity squamous cell carcinoma

Abstract: Background and Objectives The management of the clinically N0 (cN0) neck is controversial for early stage squamous cell carcinoma of the oral cavity (OSCC). This paper represents a single institution series analyzing the efficacy of sentinel lymph node biopsy (SNB) for early stage oral cavity cancers. Methods From 2005 to 2017, 108 patients with cN0 OSCC were treated with primary resection and SNB. Patients with positive biopsy results proceeded to neck dissection with or without adjuvant chemoradiotherapy. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…In addition, preoperative lymphoscintigraphy with intraoperative gamma probe SLN localization can help detect atypical lymph drainage patterns. This technique shows promise for detecting SLN cancer that could possibly be missed in END 59 . Considering SROC and the SROC AUC, SNL should be considered for its accuracy diagnosing occult metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preoperative lymphoscintigraphy with intraoperative gamma probe SLN localization can help detect atypical lymph drainage patterns. This technique shows promise for detecting SLN cancer that could possibly be missed in END 59 . Considering SROC and the SROC AUC, SNL should be considered for its accuracy diagnosing occult metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Sentinel lymph node biopsy (SLNB) has also been studied for management of cN0 necks in early stage oral cavity and oropharyngeal SCC. Loree et al studied oral cavity SCC with cN0 necks in 108 patients and found a sensitivity of 75% and negative predictive value of 91% 17 . A retrospective analysis of the National Cancer Data Base reported reduced hospital stay and morbidity of SLNB patients compared to elective neck dissection, with no significant difference in overall 3 year survival 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of oral cavity lesions have drainage into ipsilateral neck levels I, II, and III, SLNB can identify the minority of patients with aberrant lymphatic drainage or skip metastases. Loree et al found 10% of positive SLNBs were found in levels IV/IV and/or the contralateral neck. Other studies have quoted rates of 4.4% .…”
Section: Identify Unexpected Lymphatic Drainage Patternsmentioning
confidence: 99%
“…The study by Loree et al reviews their experiences with 108 patients with clinically N0 oral cavity cancers. Interestingly, the underlying rate of nodal disease was similar to the RCT mentioned above.…”
mentioning
confidence: 99%